Prohibition of Child Labour in India: Addressing the global issue of child labour with a focus on India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Child work alludes to the work of children in any work that denies children of their childhood, meddles with their capacity to go to ordinary school, and that is mentally, physically, socially or ethically risky and harmful. Of an expected 215 child workers around the world roughly 114 million (53) are in Asia and the Pacific 14 million (7) live in Latin America and 65 million (30) live in sub-Saharan Africa. Worldwide number of children in child work has declined by 33 since 2000, from 246 million to 168 million children. The greater part of them, 85 million, are in perilous work (down from 171 million of every 2000). The main aim of this paper is to prohibition of child laour in India. Asia and the Pacific still has the largest numbers (almost 78 million or 9.3 of child population), but Sub-Saharan Africa continues to be the region with the highest incidence of child labour (59 million, over 21).There are 13 million (8.8) of children in child labour in Latin America and the Caribbean and in the Middle East and North Africa there are 9.2 million (8.4).Agriculture remains by far the most important sector where child labourers can be found (98 million, or 59), but the problems are not negligible in services (54 million) and industry (12 million) – mostly in the informal economy. Child labour among girls fell by 40 since 2000, compared to 25for boys.